Overlooked and underutilized: People with disabilities are an untapped human resource - Lengnick‐Hall, Mark L.; Gaunt, Philip M.; Kulkarni, Mukta (Human Resource Management, 2008)
AbstractThe retirement of baby boomers along with a smaller cohort group of young people replacing them poses a challenge for employers in the future—where will they find the workers they need? One largely untapped source of human resources is people with disabilities (PWDs). Why have employers mostly ignored this large labor pool? This research used a semistructured interview approach with 38 executives across a broad array of industries and geographic regions to examine why employers don't hire PWDs and what they believe can be done to change this situation. Results show that most employers are not very proactive in hiring PWDs and that most employers hold stereotypical beliefs not supported by research evidence. © 2008 Wiley Periodicals, Inc.